Spillover Effects in Disclosure-Related Securities Litigation - Donelson, Dain C.; Flam, Rachel W.; Yust, Christopher G. (The Accounting Review, 2022)
ABSTRACT Securities litigation is relatively rare, but can significantly affect sued firms. We extend this research by examining the spillover effect of securities litigation on industry peers using a sample of disclosure-related litigation—distinct from events such as restatements and SEC enforcement. We find investors respond immediately as peers exhibit negative abnormal returns before and after case filings. Additionally, peers provide more voluntary earnings and sales forecasts. Notably, investors and peers respond primarily to cases that eventually settle, where litigation costs are concentrated. Further, disclosure results are concentrated in growth firms, where voluntary disclosure is most important, and in low-litigation industries, where litigation is more noteworthy. Peers also adjust attributes of mandatory disclosures: disclosures become shorter, more readable, and contain fewer litigation-related terms. These changes appear successful as peers have lower future litigation incidence. Collectively, our findings indicate securities litigation has significant effects beyond the firms that directly face litigation. JEL Classifications: D82; G30; H26; K22; K41; M41.